A questão das funções mentais superiores em Jean-Baptiste Lamarck - Vieira, Tito Lívio Ferreira (2014)
Jean-Baptiste Lamarck s Transformism was the first theory to suggest that living beings undergo continuous transformation over long periods of time. The principles of transformist theory are elaborated in Zoological Philosophy (1809), to wit, Lamarck s best-known work. The aim of the present study was to identify the contemporary scientific ideas on the nervous system that influenced Lamarck s thought on the higher mental functions. The results show that Lamarck had recourse to notions form natural philosophy, physiology and medicine that he reworked based on ideas formulated by Encyclopedists and Ideologists